TMR Using a Free Rectus Flap after Transhumeral Amputation - Logan G. Galbraith, BA; Daniel Najafali, BS; James R. Gatherwright, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Targeted muscle reinnervation offers an approach to regain use of the affected extremity through electronic prosthesis while limiting phantom pain and neuroma limb production or pain. In this case report, we present the first reported case of leveraging the rectus flap for targeted muscle reinnervation. The case herein is of a 28-year-old woman who sustained a severe right upper extremity crush injury while being involved in a vehicular roll-over collision requiring right transhumeral amputation. Plastic surgery, orthopedic surgery, and vascular surgery were consulted to manage the right upper extremity injury.